Licensing Requirements and Occupational Mobility Among Highly Skilled New Immigrants in Canada - Banerjee, Rupa; Phan, Mai (Relations industrielles / Industrial Relations, 2014)
SummaryThe present study compares the occupational trajectories of highly skilled immigrants in regulated occupations to those outside of the regulated occupations, from their pre-migration occupation, to their first job in Canada, and to subsequent jobs. Licensing requirements are likely to affect new immigrants’ occupational trajectories since they have a direct effect on how employers assess qualifications. This study utilizes growth curve modeling (GCM) and a unique dataset that contains detailed information on new immigrants’ experiences in Canada: the Longitudinal Survey of Immigrants to Canada (LSIC).Our findings indicate that immigrants working in regulated occupations prior to migration who are unable to find jobs in regulated occupations in Canada face a significantly greater drop in occupational status when they first arrive than those working in unregulated professions in their home country. Furthermore, their occupational progression over time is not faster than that of their counterparts from unregulated professions. Those who worked in unregulated fields prior to migration but found jobs in regulated fields in Canada experience an improvement in their occupational status after migration. Lastly, for those who worked in regulated professions in their home country and were able to find jobs within regulated fields in Canada, initial occupational status scores are similar to their scores in their country of origin, and there is little change in occupational status with time in Canada.The results of this study highlight the importance of ensuring that the licensing process is made easier to navigate for new immigrants. Our findings clearly indicate that immigrants who are able to successfully enter a regulated profession soon after migration fare much better in terms of occupational status than those who are unable to become licensed.